Hybrid Pesantren in Indonesia; Analyzing the Transformation of Islamic Religious Education in the Digital Age - Mustofa, Mahmud Yunus; Mas'ud, Abdurrahman; Elizabeth, Misbah Zulfa (Universitas Islam Negeri Raden Intan Lampung, 2023)
The involvement of Pesantren in digital media has led to the emergence of a brand-new Pesantren map in Indonesia, where Pesantren had previously played a traditional setting. Their engagement of religious leaders and institutions in cyberspace has fundamentally changed not only religious education practice but also the religious authority in digital media. This article aims to examine how the development of digital technology has altered the Pesantren learning tradition. Ngaji in the pesantren tradition, which is typically performed face-to-face, is currently conducted in a hybrid format through digital media. This article applied Netnography method which involves the systematic observation, analysis, and interpretation of online data. Based on Pierre Bordieau's structural construction theory, this study examines how individuals' habitus, shaped by digital media influences their engagement with digital Islamic practices. In line with that, the hybridization practiced by pesantren in Indonesia has become the new habitus of the pesantren learning tradition. Habitus is the collective entity by which and which dominant social and cultural conditions are established and reproduced. Furthermore, the Pesantren hybrid with its live-streaming Ngaji also constitutes a new Islamic public sphere that strengthens the existing Digital Islam in Indonesia. On the other hand, according to this study, the Kiai has transformed from “the cultural broker” to